AN EXPERIMENTAL EVALUATION OF FIBER REINFORCED POLYPROPYLENE THERMOPLASTICS FOR AEROSPACE APPLICATIONS (Journal of Mechanical Engineering, 2014)
Fiber reinforced thermosetting composites have wide scope in the field of Aerospace and MilitaryApplications. These materials exhibit high strength and high stiffness, besides these composites have long fatiguelife, corrosion resistance, environmental stability, thermal insulation and conductivity. Researchers areexploring possibilities to use natural fiber reinforced polymer composites (NFRPCs) in response to the increasingdemand for environmentally friendly materials and also to develop reusable fiber reinforced thermoplastics withthe desire to reduce the cost and to promote the replacement of thermosetting composites.In this work efforts are put to fabricate fiber thermoplastics made of jute, glass and carbon with (PP)polypropylene as the matrix. The mechanical strength of these fiber reinforced thermoplastics was evaluated andcompared with that of fiber reinforced thermosetting polymers made of same fibers along with epoxy matrix. Thetests clearly indicate that the laminates made of fiber reinforced polypropylene have 7 to 8 times less strengthcompared to thermosetting polymers made of fiber epoxy and it is found that for achieving better strength of thematerial, the polypropylene layers should be more than that of the epoxy matrix or to use alternative thermoplasticmaterials like polyphenylene sulfide (PPS), polyetherimide (PEI) and polyetheretherketone (PEEK). Hence thesematerials are feasible for fabricating low load bearing aircraft interior cabin parts and automobile interiorswhich can be reused or reshaped making them easy to re-work and repair.DOI: http://dx.doi.org/10.3329/jme.v43i2.17832